Composition dependent mechanical behaviour of S53P4 bioactive glass putty for bone defect grafting. (May 2017) - van Gestel, N.A.P.; Hulsen, D.J.W.; Geurts, J.; Hofmann, S.; Ito, K.; Arts, J.J.; van Rietbergen, B.
Abstract: To improve the handling properties of S53P4 bioactive glass granules for clinical applications, bioactive glass putty formulations were developed. These formulations contain both granules and a synthetic binder to form an injectable material that is easy to shape. To explore its applicability in load-bearing bone defect grafting, the relation between the putty composition and its mechanical behaviour was assessed in this study. Five putty formulations with variations in synthetic binder and granule content were mechanically tested in confined compression. The results showed that the impaction strains significantly decreased and the residual strains significantly increased with an increasing binder content. The stiffness of all tested formulations was found to be in the same range as the reported stiffness of cancellous bone. The measured creep strains were low and no significant differences between formulations were observed. The stiffness significantly increased when the samples were subjected to a second loading stage. The residual strains calculated from this second loading stage were also significantly different from the first loading stage, showing an increasing difference with an increasing binder content. Since residual strains are detrimental for graft layer stability in load-bearing defects, putty compositions with a low binder content would be most beneficial for confined, load-bearing bone defect grafting. Graphical abstract: